A visibilidade lésbica nas pedagogias do cinema - Paulino, Alessandro Garcia (2019)
The present study focuses on the themes of gender and sexualities in the cinema, with the aim of analyzing the Brazilian cinematographic productions that approach in their narrative the lesbianities. The investigative paths conducted on this study led to a survey of films consulted on public domain repositories, and also the theoretical and technical works of the studies on the cinema were used to think how image pedagogies produce discourses on lesbianity. Nine (9) films from 2000 to 2016 were cataloged. These nine films selected went through the following new inclusion criteria: films that have lesbian narratives without some form of heterosexual amorous trios, or some type of male fetishization between the affective moments lived by the characters of the films, and films that present a lesbian protagonism or antagonism as part of the watched films. Through this process, the following two films were selected in the final stage of the research: Flores Raras (2013) and Como Esquecer (2010). The main hypothesis raised would be the invisibility and silencing of the lesbian character in Brazilian cinema because of the scarce production in the area. Finally, we obtained through analyzes of Flores Raras (2013) and Como Esquecer (2010) considerations about the perspective of visibility, in which the Brazilian cinema has established on the lesbianities a formula that conveys an exacerbated suffering of the characters as if the processes of resistance were extremely diffuse and complex mechanisms in the relations.